Maternal Mortality in Cardiac Pregnancy: Ethical Conflicts in Patient Autonomy and Clinical Decision-Making - Hanifan Nugraha; Muhammad Alamsyah Aziz; Dini Pusianawati (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Maternal mortality remains a significant concern in pregnancies complicated by heart disease, especially when patient preferences diverge from evidence-based clinical recommendations. These situations present complex clinical and ethical challenges for healthcare providers. This case report illustrates the interplay between patient autonomy, clinical decision-making, and outcomes in high-risk cardiac pregnancy. A 34-year-old multiparous woman with known cardiomegaly and valvular heart disease presented at 37-38 weeks' gestation with worsening dyspnea, cardiac decompensation, and pulmonary hypertension. Despite medical advice recommending immediate delivery at a tertiary care center, she initially declined intervention. She later returned with severe preeclampsia and pulmonary hypertension. An emergency caesarean section was performed, but her condition deteriorated postoperatively, culminating in cardiac arrest and death. This case underscores the ethical tension between honoring patient autonomy, the right to make informed decisions, and the principle of beneficence, which obligates clinicians to act in the patient's best interest. Decision-making was shaped by educational background, limited health literacy, cultural norms, family influence, and potential mistrust of the healthcare system, all of which may compromise truly informed consent. Addressing these barriers requires clear, accessible, and culturally attuned communication to ensure patients comprehend the risks and benefits. Integrating structured shared decision-making and early ethics consultation can help resolve conflicts, align care with patient values, and safeguard maternal and fetal outcomes. Ethical management demands a careful balance between respecting autonomy and preventing harm, while advocating for systemic reforms that address the social determinants of maternal health. Timely multidisciplinary care, culturally sensitive counseling, and structured shared decision-making are essential to harmonize patient autonomy with life-saving interventions in high-risk cardiac pregnancies, thereby reducing preventable maternal mortality. Keyword: Ethical Dilemmas, Maternal Mortality, Cardiac Disease In Pregnancy.